The Emerging Evidence of the Parkinson Pandemic - Dorsey, E. Ray; Sherer, Todd; Okun, Michael S.; Bloem, Bastiaan R. (Journal of Parkinson's disease, 2018)
Neurological disorders are now the leading source of disability globally, and the fastest growing neurological disorder in the world is Parkinson disease. From 1990 to 2015, the number of people with Parkinson disease doubled to over 6 million. Driven principally by aging, this number is projected to double again to over 12 million by 2040. Additional factors, including increasing longevity, declining smoking rates, and increasing industrialization, could raise the burden to over 17 million. For most of human history, Parkinson has been a rare disorder. However, demography and the by-products of industrialization have now created a Parkinson pandemic that will require heightened activism, focused planning, and novel approaches.